2015
DOI: 10.1513/annalsats.201504-190oc
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Duration and Metabolic Syndrome. An Updated Dose–Risk Metaanalysis

Abstract: Rationale: Several studies have reported that both short and long sleep durations are associated with the metabolic syndrome, but whether a dose-response relationship exists is unclear.Objectives: We performed a metaanalysis to study the magnitude of the association between the different durations of sleep and metabolic syndrome. Methods:We searched in the databases of PubMed, Web of Science, and Ovid (all Journals@Ovid) from inception to October 4, 2014 for cross-sectional studies where an association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
87
3
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(104 citation statements)
references
References 51 publications
6
87
3
4
Order By: Relevance
“…Interestingly, one study found that after adjusting for confounders, long (≥9 hours) but not short (<6 hours) sleep duration was associated with an increased risk of the MetS 76. A recent meta-analysis of 18 studies encompassing 75,657 participants and using adults sleeping for 7–8 hours as a reference group found a dose–response relationship between sleep duration and the MetS, with increasing risk of the MetS in sleep categories all the way up to a 1.5-fold OR (95% CI 1.1–2.08, P =0.01) among those sleeping for <5 h/night; however, they did not find a significant association between long sleep duration and the MetS – OR 1.13 (95% CI, 0.97–1.32; P =0.10) 71. The question of causality is difficult to assess in cross-sectional studies; however, a prospective cohort study of 2,579 adults aged 40–70 years without MetS at baseline, who were followed for an average of 2.6 years, found a significantly higher risk of incident MetS for those sleeping for <6 hours – adjusted OR (95% CI) 1.41 (1.06–1.88).…”
Section: Sleep Restriction and Sleep Architecture: Impact On The Metsmentioning
confidence: 87%
“…Interestingly, one study found that after adjusting for confounders, long (≥9 hours) but not short (<6 hours) sleep duration was associated with an increased risk of the MetS 76. A recent meta-analysis of 18 studies encompassing 75,657 participants and using adults sleeping for 7–8 hours as a reference group found a dose–response relationship between sleep duration and the MetS, with increasing risk of the MetS in sleep categories all the way up to a 1.5-fold OR (95% CI 1.1–2.08, P =0.01) among those sleeping for <5 h/night; however, they did not find a significant association between long sleep duration and the MetS – OR 1.13 (95% CI, 0.97–1.32; P =0.10) 71. The question of causality is difficult to assess in cross-sectional studies; however, a prospective cohort study of 2,579 adults aged 40–70 years without MetS at baseline, who were followed for an average of 2.6 years, found a significantly higher risk of incident MetS for those sleeping for <6 hours – adjusted OR (95% CI) 1.41 (1.06–1.88).…”
Section: Sleep Restriction and Sleep Architecture: Impact On The Metsmentioning
confidence: 87%
“…The results of the conducted tests show no dependency between short sleep duration (≤ 6 h) and the risk of MetS, despite the fact that many authors have confirmed the presence of such dependencies [9, 12-15, 21, 32]. It should be mentioned, however, that most of these papers applied different definitions of MetS [9,[12][13][14]32], and in some there were also definitions of short sleep duration applied which was less than 6 h per night [15,21]. Long sleep duration (≥ 9 h) was connected with a higher risk of MetS, but only in the unadjusted model.…”
Section: Discussionmentioning
confidence: 92%
“…Some of them show a U-shaped relationship between sleep duration and the prevalence of MetS [10]. It has been shown in some papers that MetS is only associated with short sleep duration [12][13][14][15] or long sleep duration [16][17][18]. In another paper, however, there was no relationship found between sleep duration and the risk of MetS [19].…”
Section: Introductionmentioning
confidence: 99%
“…대사증후군의 위험인자는 연령, 유전, 폐경상태, 인종, 비만, 흡연, 소득, 탄수화물 섭취량, 신체활동 [8], 고혈압 등의 가족력 [9], 지각된 스트레스, 우울, 자살생각 및 수면시간 등의 정신심 리적 요인 [10], 백혈구와 적혈구수 [11] 등으로 알려져 있다. 수 면부족은 탄수화물 식품에 대한 식욕을 증진시키고 인슐린 저 항성을 높여 대사증후군의 발생 위험을 높이며 [10], 우울 등의 정신심리적 요인은 좋지 않은 식습관, 수면 장애, 신체활동 저 하 등과 관련되어 대사증후군의 발생 위험을 높이는 것으로 보 고되고 있다 [12].…”
unclassified
“…수 면부족은 탄수화물 식품에 대한 식욕을 증진시키고 인슐린 저 항성을 높여 대사증후군의 발생 위험을 높이며 [10], 우울 등의 정신심리적 요인은 좋지 않은 식습관, 수면 장애, 신체활동 저 하 등과 관련되어 대사증후군의 발생 위험을 높이는 것으로 보 고되고 있다 [12]. 백혈구와 적혈구 수의 증가 또한 인슐린 저항 상태와 관련되어 대사증후군 발생 위험을 증가시키는 경향이 있다 [11].…”
unclassified